Malpractice Litigation Related to Diagnosis and Treatment of Intracranial Aneurysms - Khan, A.; Khunte, M.; Wu, X.; Bajaj, S.; Payabvash, S.; Wintermark, M.; Matouk, C.; Seidenwurm, D.J.; Gandhi, D.; Parizel, P.; Mezrich, J.; Malhotra, A. (American Journal of Neuroradiology, 2023)
BACKGROUND AND PURPOSE: Approaches to management of intracranial aneurysms are inconsistent, in part due to apprehension relating to potential malpractice claims. The purpose of this article was to review the causes of action underlying medical malpractice lawsuits related to the diagnosis and management of intracranial aneurysms and to identify the factors associated and their outcomes.MATERIALS AND METHODS: We consulted 2 large legal databases in the United States to search for cases in which there were jury awards and settlements related to the diagnosis and management of patients with intracranial aneurysms in the United States. Files were screened to include only those cases in which the cause of action involved negligence in the diagnosis and management of a patient with an intracranial aneurysm.RESULTS: Between 2000 and 2020, two hundred eighty-seven published case summaries were identified, of which 133 were eligible for inclusion in the analysis. Radiologists constituted 16% of 159 physicians sued in these lawsuits. Failure to diagnose was the most common medical malpractice claim referenced (100/133 cases), with the most common subgroups being “failure to include cerebral aneurysm as a differential and thus perform adequate work-up” (30 cases), and “failure to correctly interpret aneurysm evidence on CT or MR imaging” (16 cases). Only 6 of these 16 cases were adjudicated at trial, with 2 decided in favor of the plaintiff (awarded $4,000,000 and $43,000,000, respectively).CONCLUSIONS: Incorrect interpretation of imaging is relatively infrequent as a cause of malpractice litigation compared with failure to diagnose aneurysms in the clinical setting by neurosurgeons, emergency physicians, and primary care providers.IAintracranial aneurysm